2022
DOI: 10.1101/2022.09.26.508121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical, socio-demographic, and parental correlates of early autism traits in a community cohort

Abstract: Importance: Autism traits typically emerge between the ages of 1 and 2. It is not known if experiences which increase the likelihood of childhood autism are related to early trait emergence, or if other exposures are more important. Identifying factors linked to toddler autism traits may improve our understanding of the mechanisms underlying atypical neurodevelopment. Objective: To characterise the association between 18-month autism traits and clinical, socio-demographic, and parental factors. Design: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…However, multiples studies have shown that family psychosocial and socio-demographic factors have a significant impact on brain development in childhood; with factors such as maternal stress, depression, low education, maternal immigration status, maternal age greater than 35 years, paternal age over 38 years and low household income all being linked to poorer developmental outcomes [87][88][89][90][91] . Thus, further studies could benefit from evaluating links between these wider socio-demographic markers and brain dynamics in early childhood 92 .…”
Section: Discussionmentioning
confidence: 99%
“…However, multiples studies have shown that family psychosocial and socio-demographic factors have a significant impact on brain development in childhood; with factors such as maternal stress, depression, low education, maternal immigration status, maternal age greater than 35 years, paternal age over 38 years and low household income all being linked to poorer developmental outcomes [87][88][89][90][91] . Thus, further studies could benefit from evaluating links between these wider socio-demographic markers and brain dynamics in early childhood 92 .…”
Section: Discussionmentioning
confidence: 99%
“…However, multiples studies have shown that family psychosocial and socio-demographic factors have a significant impact on brain development in childhood; with factors such as maternal stress, depression, low education, maternal immigration status, maternal age greater than 35 years, paternal age over 38 years and low household income all being linked to poorer developmental outcomes (Deave et al, 2008; Dollaghan et al, 1999; Gale-Grant et al, 2020; Glover and O’Connor, 2002; Leonard et al, 2011; Rice et al, 2010; To et al, 2004). Thus, further studies could benefit from evaluating links between these wider socio-demographic markers and brain dynamics in early childhood (Gale-Grant et al, 2022).…”
Section: Discussionmentioning
confidence: 99%